The Effect of Cocoa Beans Fermentation on Processed Chocolate In West Kalimantan - H, Jhon David; P, Tommy (Biopropal Industri, 2011)
Research studies of fermentation effects on processed chocolate have been made. The purpose of this study was to see the effect of different levels of fermentation of cocoa preparations (pasta, fats and powder) to the chemical quality and flavor. Harvested Cocoa beans will be treated fermentation. The treatment used was the time of fermentation namely: (A) Non fermentation, (B) Imperfect fermentation (4 days) and (C) Perfect fermentation (5 days). The parameters observed was: (a) chemical quality namely water content, fat content, pH, (b) organoleptic tests namely color, aroma, taste bitter (bitterness), texture. The results showed that fermentation of cocoa beans have real impact on levels of fat, water content and pH. Panelists gave the highest rankings for quality of organoleptic attributes of pasta, fat and chocolate powder from perfectly fermented beans. Processing of cocoa beans into refined products had levels of depreciation for each stage. 100 kg dried cocoa beans could produce 79.0 kilograms of chocolate paste, 48.7 kg of cocoa powder, and 26.5 kg of fat. Fermentation for 5 days is the best solution to improve the quality of processed chocolate.